International business control, reporting and corporate governance - Nurdin, Georges
This book is for CEOs, CFOs, International Business Managers, Controllers, International Project Directors, Board Members, Consultants, Investment Bankers and Business Students. Have you ever felt that, despite expensive converging systems and models, managing, controlling, reporting, and governing successfully internationally and across cultures takes more than filling out standard check lists? Then this book is for you. . Identify and monitor the 12 key drivers that ultimately lead to sustained international performance, across cultures, countries and sectors. Understand why 75 % of international M&As fail, and how to remedy these massive value depletion factors. Adjust your organisational structures to best fit the local cultures to get the best global performance from your operations. Get a culturally efficient reporting system that helps you understand what is really happening in remote locations beyond the avalanche of numbers, be they US, GAAPs or IFRS compliant. Identify the best controlling model and mode for the country/region you are operating in and the phase of international dynamics you are engaging in. Specify the right controller profile for different international assignments, for example joint ventures, multi-country and multi-stakeholder projects. Establish an efficient business dialogue with all international components of your group to ensure you are truly in control. Compose your board and set adequate governance and monitoring systems that will help you leverage most from your international operations.